2017
DOI: 10.3389/fphar.2017.00359
|View full text |Cite
|
Sign up to set email alerts
|

Azelaic Acid Exerts Antileukemic Activity in Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is an acute leukemia common in most adults; its prevalence intensifies with age. The overall survival of AML is very poor because of therapeutic resistance. Azelaic acid (AZA) is non-toxic, non-teratogenic, and non-mutagenic and its antitumor effect on various tumor cells is well established; Nonetheless, its therapeutic effects in AML cells are largely unknown. In this study, it was shown that AZA significantly inhibits the cell viability and induces apoptosis in AML cells in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Mitochondrial damage results in mitochondrial ROS production, which upregulates the expression of p53, which promotes mitochondria-mediated apoptosis [ 81 ]. In fact, it has recently been confirmed that AZA induces apoptosis in acute myeloid leukaemia cells in a dose-dependent manner [ 82 ]. Thus, AZA shares mechanistic similarities with peroxide-induced mitochondrial disturbances upregulating the p53 response.…”
Section: Azelaic Acidmentioning
confidence: 99%
“…Mitochondrial damage results in mitochondrial ROS production, which upregulates the expression of p53, which promotes mitochondria-mediated apoptosis [ 81 ]. In fact, it has recently been confirmed that AZA induces apoptosis in acute myeloid leukaemia cells in a dose-dependent manner [ 82 ]. Thus, AZA shares mechanistic similarities with peroxide-induced mitochondrial disturbances upregulating the p53 response.…”
Section: Azelaic Acidmentioning
confidence: 99%
“…Acute myeloid leukaemia (AML) is a heterogeneous group of disorders characterized by the clonal proliferation of progenitor cells or primitive hematopoietic stem cells (1). Due to the development of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for patients with AML, in particular the extensive development of haploidentical allo-HSCT in China, the therapeutic efficacy of treatments for AML have significantly improved throughout previous decades (2). However, the treatment of refractory and relapsed patients remains a significant clinical challenge that has yet to be overcome (3).…”
Section: Introductionmentioning
confidence: 99%
“…Azelaic acid is a naturally occurring saturated dicarboxylic acid derived from a variety of grains such as sorghum ( Sorghum bicolor ) [66], rye ( Secale cereal ) [67]. This compound has also been reported to exert a variety of biological activities in vitro and in vivo including antimicrobial [46] and antitumor [47,48] capabilities. The U.S. Food and Drug Administration (FDA) approved 15% gel formulation of azelaic acid for the treatment of rosacea in 2002 [68] and this compound is an excellent antimicrobial agent cosmetic for the treatment of comedonal and inflammatory acnes [69,70].…”
Section: Discussionmentioning
confidence: 99%